Evaluation of a non-isolated charger. Concept, analysis and reference design. - Nyström, Robert; He, Yuxuan (My University, 2012)
This report discusses the necessity of a galvanic isolation in an onboard charger for a Plug-in Hybrid Electric Vehicle. It was hypothesized that the galvanic isolation was a source of losses, and it is known that the use of galvanic isolation give rise to higher costs and it requires more space. Three different topologies without galvanic isolation was investigated and simulated in OrCad PSpice. For these, cost, volume, weight and efficiency was analyzed and a best solution was chosen. It was found that using a bridgeless charger gave the highest efficiency, approximately 98%, and it also had acceptable price and a satisfactory dimensional analysis. The bridgeless charger did however not perform good regarding THD injected into the utility, thus future work with this charger is needed to investigate if it is possible to reduce the THD impact without influencing the efficiency, size and weight to much. Synchronous rectification was also investigated and it was found that it was not a good solution in this case.
Keywords: Elkraftteknik; Electric power engineering